Impact de nouvelle stratégie sur l’enseignement-apprentissage du français langue étrangère (FLE) Cas de la compréhension de l’écrit chez des apprenants de 3èmeAP À l'école Houari BOUMEDIENE Sidi Aissa à M’Sila - ZINE SOUNDES, DJOUBAR AhmedMESSEGUEM ZEYNEB (université mohamed boudiaf .m'sila, 2023)
Our research work is part of the didactics of FLE writing, it is centered on the question of the impact of new pedagogical strategies on the teaching-learning of FLE in reading comprehension. First, we opted to clarify some notions related to our research theme. Indeed, we have implemented a study on the basis of an analysis of the answers of the written tests of the learners of the 3rd AP of the HOUARI BOUMEDIENE School located in SIDI AISSA, by identifying the development of a new program. The answers obtained from the tests addressed to the learners mainly concern the use of the new pedagogical strategy in the FLE class which refers to the service of good command of written comprehension as well as other linguistic skills
Keywords: reading comprehension, teaching-learning, the learners